THE EFFECT OF INFLATION, MINIMUM WAGE, LABOR ABSORPTION AND THE COVID-19 PANDEMIC ON POVERTY IN INDONESIA - Rahma Viona Angraeni; Siti Nurjanah; Sri Indah Nikensari (Publikasi Inspirasi Indonesia, 2024)
Poverty is still the most important problem in Indonesia, especially in urban areas. The problem of urban poverty is long-term, making it difficult to overcome until now. The increase in urban poverty is often characterized by underdevelopment and backwardness, low productivity and low income received, and the ability and opportunity to develop themselves and improve their welfare. The Covid-19 pandemic also has an impact not only on health but also on urban poverty. There are several factors that cause urban poverty such as high inflation rates, low wages, low employment and Covid-19 Pandemic. The purpose of this study is to determine the effect of Inflation, Minimum Wage, Labor Absorption, and The Covid-19 Pandemic on Urban Poverty in Indonesia. This research uses quantitative methods with multiple linear regression analysis techniques and the Generalized Least Square (GLS) model. This research uses secondary data and the Covid-19 pandemic is categorized as a dummy variable. The results of this study show that inflation has no significant effect on urban poverty. Minimum wage and labor absorption have a negative and significant effect on urban poverty. Meanwhile, the Covid-19 pandemic has a positive and significant effect on urban poverty.